The Influence of Financial Performance on Company Value in Manufacturing Companies in the Food and Beverage Sector in the 2019-2021 Period - Dewi Puspita; Muchriana Muchran (CV. AFDIFAL MAJU BERKAH, 2023)
This study aims to determine the effect of performance on the company's financial value. This study uses a quantitative approach with secondary data sources obtained from the official IDX website. The samples used in this study were 23 companies in the Food and Beverage Subsector for the 2019-2021 period which were obtained using the Purposive Sampling method. The variables used in this study are Profitability (ROA), Liquidity (CR) and company value (TobinQ). The data analysis technique in this study uses multiple linear techniques. The results of the study concluded that partially Profitability has no significant effect on firm value. This shows that the amount of profits earned by the company does not affect the value of the company. Partially, liquidity has no significant effect on firm value, this indicates that companies with high or low liquidity do not affect firm value. Because the company uses most of its money to pay its obligations.